2021
DOI: 10.3390/app11209477
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Thermal-Flow Characteristics in Heat Exchanger with Various Tube Shapes

Abstract: In this study, eight configurations of oval and flat tubes in annular finned-tube thermal devices are examined and compared with the conventional circular tube. The objective is to assess the effect of tube flatness and axis ratio of the oval tube on thermal-flow characteristics of a three-row staggered bank for Re (2600 ≤ Re ≤ 10,200). It has been observed that the thermal exchange rate and Colburn factor increase according to the axis ratio and the flatness, where O1 and F1 provide the highest values. O1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For global searches, the new states of their agents are determined by the randomly selected search agent rather than the best-known state. Global searching is shown in Model Equations ( 18) and (19). In the equations, → X rand is the randomly picked search agent [28].…”
Section: Prey Exploration (Global Searching)mentioning
confidence: 99%
See 1 more Smart Citation
“…For global searches, the new states of their agents are determined by the randomly selected search agent rather than the best-known state. Global searching is shown in Model Equations ( 18) and (19). In the equations, → X rand is the randomly picked search agent [28].…”
Section: Prey Exploration (Global Searching)mentioning
confidence: 99%
“…Apart from the studies mentioned above, many studies involve heat transfer optimization [16][17][18][19][20][21][22]. When evaluated in general, it has been seen that numerical optimization solutions and basic heuristic optimization techniques are used in heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds number used in this study, which is dependent on the outside diameter of the tube collar, D c = D t + 2d f , and the maximum speed at the smallest free flow crosssection u max ranges from 4400 to 14300. This results in the airflow being incompressible, turbulent, steady-state, and 3-D [19][20][21][22]. Based on previous research for annular fins [15, 16,…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…For the case of natural convection thermal exchange, Unger et al [10] analyzed the impact of flat-tube shapes and dimensions on thermal-flow characteristics for four rows of annular FTHEs. It was found that, for staggered tube arrangement, the conventional circular tube and flat tube pattern (with an axis ratio of 1:2.1) gives the highest heat exchanger efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the majority of research studies have separately investigated the effect of tube ellipticity and flatness in FTHEs. Also, only Zeeshan et al [1] and Djeffal et al [10] numerically analyzed the heat transfer and flow physics in FTHEs using circular, oval, and flat shapedtubes, whereas, in the case of sinusoidal wavy FTHEs, no research has been done on the influence of these tube forms. Hence, the purpose here is to examine the influence of tube shapes with sinusoidal wavy fins for two-row staggered bundles using the RNG k   turbulence model of ANSYS FLUENT 18.2.…”
mentioning
confidence: 99%